Cold Exposure and Health Effects Among Frozen Food Processing Workers in Eastern Thailand - Anamai Thetkathuek; Tanongsak Yingratanasuk; Wanlop Jaidee; Wiwat Ekburanawat (Elsevier, 2015)
Frozen food processing workers work under a cold environment which can cause several adverse health effects.This study explored factors affecting workers' health in the frozen food industry in Thailand. Participants comprised 497 workers exposed to a cold working environment and 255 office workers who served as the controls. Data were collected by a survey on the work environment, and the interview of workers for abnormal symptoms. The exposed group had the following characteristics: 52.7% male, overall average age of 27 (SD 6.6) years old, attained elementary education (Grade 4 and Grade 6) (54.1%), married (48.9%), smokers (21.3%), alcohol consumption (31.0%), duration of work was between 1 and 5 years (65.2%), working 6 days a week (82.7%), 1-5 hours of overtime per week (33.8%), office workers (33.9%); work category: sizing (6.9%), peeling (28.3%) dissecting (22.2%), and in the warehouse (8.6%). The temperature in the work environment ranged from 17.2°C to 19.2°C in most sections, −18.0°C in the warehouse, and 25°C in the office areas. Warehouse workers had more abnormal symptoms than controls including repeated pain in the musculoskeletal system (OR 11.9; 95% CI 6.12-23.45), disturbance throughout the body (OR 4.60; 95% CI 2.00-10.56), respiratory symptoms (OR 9.73; 95% CI 3.53-26.80), episodic finger symptoms (OR 13.51; 95% CI 5.17-35.33). The study results suggest that workers' health should be monitored especially with regard to back and muscle pain, respiratory symptoms, episodic finger symptoms, and cardiovascular symptoms. Health promotion campaigns such as antismoking and reduction of alcohol consumption should be established because smoking and alcohol consumption are contributing factors to the pathogenesis of Raynaud's phenomenon and peripheral vascular disorders such as hypertension and heart disease.